Excision of Fibroadenoma with an Upper Incision Compared To the Periareolar Incision - Nayab Batin Farooqi, Samia Naseer, Hafiz Abdul Hanan Atari, Varda Balouch, Romasa Muzaffar Ali Joyo, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Breast fibroadenomas are removed traditionally with overlying incision on the tumor. The peri-areolar incision is a new and cosmetically important development for fibroadenomas excision. Aim: The aim of the analysis is to assess the peri-areolar method of excision of fibroadenoma. Place and Duration: In the surgical department of Benazir Bhutto Hospital and DHQ Hospital Rawalpindi for one-year duration from June 2020 to May 2021. Methods: The patients were selected by non-randomized technique and clinical data from 40 patients (Group A) who underwent excision of fibroadenoma via a peri-areolar incision and 42 patients who underwent the overlying technique of incision were analyzed retrospectively, and the parameters were evaluated such as the duration of the operation, the overall cosmetic outcomes and postoperative complications. The peri-areolar incision technique is explained in relations of indications and the surgical technique. Results: The use of the peri-areolar technique resulted in faster postoperative complications (4/40 vs 2/40, p = 0.072). The 6-month follow-up exhibited that the subjects who experienced peri-areolar procedure had improved cosmetic results (95% group A vs 71.4% group B, p = 0.001). Conclusions: Peri-areolar incision gives improved cosmetic results compared to the overlying technique of incision, at the expense of minor postoperative complications.